Oxidative response of polymorphonuclear leucocytes to synovial fluids from patients with rheumatoid arthritis - Dularay, B; Badesha, J S; Dieppe, P A; Elson, C J (Annals of the rheumatic diseases, 1990)
Only a minority (7/35, 20%) of synovial fluids from patients with rheumatoid arthritis (RA) and none from patients with other arthritides stimulated the oxidative response of polymorphonuclear leucocytes (PMNs). Superoxide anion generation was measured by superoxide dismutase inhibitable reduction of cytochrome c. The same synovial fluids stimulated superoxide release by PMNs regardless of their source, though they elicited a greater response from RA synovial fluid PMNs than from either RA blood PMNs or blood PMNs from normal subjects. The remaining synovial fluids failed to stimulate any of the PMNs, though some (2/10) stimulated PMNs pretreated with cytochalasin B. The stimulatory activity was removed from RA synovial fluids by protein A-Sepharose and eluted with the void volume on gel chromatography. It is considered that immunoglobulin aggregates in some RA synovial fluids may stimulate the oxidative response of PMNs in the joint space but that most do not because these fluids contain either a specific inhibitor or immunoglobulin aggregates of an inappropriate type, or both.